Absence of lymphangiogenesis and intratumoural lymph vessels in human metastatic breast cancer - Williams, Cory SM; Leek, Russell D; Robson, Alistair M; Banerji, Suneale; Prevo, Remko; Harris, Adrian L; Jackson, David G (The Journal of pathology, 2003)
Early metastasis to lymph nodes is a frequent complication in human breast cancer. However, the extent to which this depends on lymphangiogenesis or on invasion of existing lymph vessels remains controversial. Although proliferating intratumoural lymphatics that promote nodal metastasis have been demonstrated in experimental breast tumours overexpressing VEGF‐C, it has yet to be determined whether the same phenomena occur in spontaneous human breast cancers. To address this important issue, the present study investigated the lymphatics in primary human breast carcinoma (75 cases of invasive ductal and lobular breast cancer) by quantitative immunohistochemical staining for the lymphatic endothelial hyaluronan receptor LYVE‐1, the blood vascular marker CD34, and the nuclear proliferation marker pKi67. None of the breast carcinomas was found to contain dividing lymph vessels, even in areas of active haemangiogenesis. Furthermore, the majority of non‐dividing lymph vessels were confined to the tumour periphery where their incidence was low and unrelated to tumour size, grade or nodal status; rather, their density was inversely correlated with tumour aggressiveness as assessed by macrophage density (p = 0.009), and blood microvessel density (p = 0.05, Spearman Rank), as well as with distance from the tumour edge. Finally, a proportion of the peritumoural lymphatics contained tumour emboli associated with hyaluronan, indicating a possible role for LYVE‐1/hyaluronan interactions in lymphatic invasion or metastasis. These results suggest that naturally occurring breast carcinomas invade and destroy lymph vessels rather than promoting their proliferation; that breast tumour lymphangiogenesis may not always occur at physiological VEGF‐C levels; and that nodal metastasis can proceed via pre‐existing lymphatics. Copyright © 2003 John Wiley & Sons, Ltd.